Cultural Mistranslation and Intercultural Communication--A Case Study of Chinese Reports on Zhai Tiantian’s Incident in the U.S.A. - Zhang, Xiaochi (International Journal for Innovation Education and Research, 2014)
Globalization enters a world in which people of different cultural backgrounds and increasingly comes to depend on one another. To understand and accept cultural differences becomes imperative to be effective in intercultural communication in global society. In this process, translation has played an important role in intercultural mass communication connecting different cultures and different nations. However, people including translators and reporters from another culture sometime misunderstood some incidents and were unbelieving what happened with the specific incident due to mistranslation which resulted in misreports from mass media. Therefore, the author will take Zhai Tiantian’s incident in the U.S.A. as a case and make further analysis of the relationship between language and culture, and the function of translation in the intercultural communication. Finally, the author also discusses how to make intercultural translation better in order to promote intercultural communication between different people from different cultural backgrounds.